FAKTOR–FAKTOR PENYEBAB TIDAK TERCAPAINYA REALISASI PENERIMAAN PAJAK SARANG BURUNG WALET DI KOTA PEKANBARU TAHUN 2016 – 2018 - Muhammad Firdaus; Erman M (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Swallow's Nest Tax, which has the potential to become a concern and target of thegovernment in collecting swallow's nest tax. nfortunately, until the end of 2018it turned out that the application of tax collection on swallow's nests had not been realized well enough. This thesis discusses how performance The Regional Government of Pekanbaru City in managing the swallow's nest tax in this case is the Regional Revenue Agency (Bappenda) of Pekanbaru City as a revenue supportfunction. The purpose of this study was to determine the factors causing the realization of swallow's nest tax revenue in Pekanbaru City not to be achieved. The theoretical concept used by the researcher is the causative factor of not achieving the Realization of Swallow's Nest Tax Revenue and the Optimization of Local Taxes. This study used a qualitative research method with descriptive data analysis. In collecting data researchers used interview echniques, observation and documentation. The results of this study can be concluded that the factors causing the failure to achieve Swallow's Nest Tax are due to lack of coordination, weak quality of personnel capabilities, as well as inaccuracy in determining basic data and lack of awareness of taxpayers. Efforts must be made by the Regional Revenue Agency of Pekanbaru City to increase nest tax revenue swiftlet namely Expanding the Acceptance base, trengthening the Collection Process and Increasing Supervision. Keywords: Swallow's Nest Tax, PAD.